Structure of MHD fluctuations in the torsatron U-3M in steady-state stage of discharge - Pashnev, V.K.; Sorokovoy, E.L.; Petrushenya, A.A.; Ozherel’yev, F.I. (Вопросы атомной науки и техники, 2018)
Study of MHD fluctuations was performed in quasi-stationary mode of weakly collisional discharge in torsatron U-3M in frequency range 0.5…70 kHz. The fluctuations of the magnetic field were detected in the following frequency ranges: 2.5…3.9, 5.9…7.2, 9.4…10.9, 14…15.9, 20…27, 39…47 kHz. It is also shown that there are standing and rotation structures. Rotation structures can rotate in the direction of both ion and electron diamagnetic drift. The poloidal structure of plasma MHD activity with wave numbers m=0; 1; 2; 3 was obtained, which made it possible to determine the level of fluctuations of the magnetic field inside the confinement volume.